FACTORS AFFECTING MANAGEMENT PERFORMANCE ACCOUNTABILITY IN PDAM TIRTANADI, AMPLAS BRANCH - Nadratun Nazmi; Elizar Sinambela (Proceeding International Seminar of Islamic Studies, 2022)
His study aims to analyze the factors that affect the accountability of management performance at PDAM Tirtanadi Amplas Branch. The type of research conducted is causal associative. The research method uses a survey method. The population in this study is partly permanent and non-permanent employees in the PDAM environment, amounting to 43 people. The entire population is used as a sample. The data were processed using multiple regression analysis and residual test. The results of this study prove that strategic planning, performance measurement, performance reporting, utilization of performance information have a significant positive effect on management performance accountability at PDAM Tirtanadi Amplas Branch. Partially.